Evaluating the effectiveness of financial management in state owned enterprises:a case of Limpopo Economic Development Agency - Masekoameng, Ramadimetja Catherine (University of Limpopo, 2016)
Refer to document
Thesis (MPA.) --University of Limpopo, 2016.
Keywords: Financial management; State-owned enterprises; Government business enterprises -- South Africa -- Finance; Government business enterprises -- Management; Government corporations -- South Africa -- Finance